Just so stories - Kipling, Rudyard, 1865-1936 (London : Puffin, 2008)
In this collection of fables, enjoy delightful tales of whales and cats and kangaroos and crabs. Venture into the High and Far-Off Times, and uncover everything from how the camel got in a humph (and got his hump!) to how the alphabet was invented. Enchanting and very funny, these fantastical stories will take you on a journey to the boundaries of reality and beyond.
How the whale got his throat -- How the camel got his hump -- How the rhinoceros got his skin -- How the leopard got his spots -- The elephant's child -- The sing-song of old man kangaroo -- The beginning of the armadilloes -- How the first letter was written -- How the alphabet was made -- The crab that played with the sea -- The cat that walked by himself -- The butterfly that stamped.
GR 6-8
Keywords: Animals -- Juvenile fiction; Animals; Short stories; Fiction; Juvenile works; Short stories